2021
DOI: 10.4132/jptm.2020.10.04
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver diagnostic reproducibility in advanced-stage endometrial carcinoma

Abstract: Background: The accurate pathologic diagnosis and subtyping of high-grade endometrial carcinoma are often problematic, due to its atypical and overlapping histopathological features. Methods: Three pathologists reviewed 21 surgically resected cases of advancedstage endometrial carcinoma. The primary diagnosis was based only on hematoxylin and eosin stained slides. When a discrepancy arose, a secondary diagnosis was made by additional review of immunohistochemical (IHC) stains. Finally, three pathologists discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Later, these subtypes were shown to be associated with specific molecular aberrations, such as microsatellite instability (MSI), and mutations in PTEN, KRAS , and CTNNB1 (beta-catenin) mutations in type 1 and TP53 , HER2 , and loss of heterogeneity in type 2 [ 53 ]. However, even among expert gynaecological pathologists, poor to moderate reproducibility was shown in subtype classification in high-grade EC, especially if diagnosis was based on haematoxylin eosin slides only [ 54 , 55 , 56 ]. Immunohistochemical analysis, in specific p53 and the oestrogen and progesterone hormone receptors (ER, PR), has for a longer time been applied to support the subtyping in less straightforward cases [ 57 ].…”
Section: Molecular Risk Classificationmentioning
confidence: 99%
“…Later, these subtypes were shown to be associated with specific molecular aberrations, such as microsatellite instability (MSI), and mutations in PTEN, KRAS , and CTNNB1 (beta-catenin) mutations in type 1 and TP53 , HER2 , and loss of heterogeneity in type 2 [ 53 ]. However, even among expert gynaecological pathologists, poor to moderate reproducibility was shown in subtype classification in high-grade EC, especially if diagnosis was based on haematoxylin eosin slides only [ 54 , 55 , 56 ]. Immunohistochemical analysis, in specific p53 and the oestrogen and progesterone hormone receptors (ER, PR), has for a longer time been applied to support the subtyping in less straightforward cases [ 57 ].…”
Section: Molecular Risk Classificationmentioning
confidence: 99%
“…However, the specified significance level narrowly missed reaching statistical significance in the two-tailed test ( p = 0.057). Interestingly, several studies have reported poor interobserver viability in endometrial cancer, particularly for high-grade tumors [ 22 24 ]. Notably, these studies focused on interobserver variability within single institutions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with considerable interobserver variation, high‐grade EC cannot be reliably classified according to histomorphologic criteria, resulting in misdiagnosis due to mixed high‐grade components in histology. 12 , 13 , 14 Moreover, stage and lymphovascular space invasion (LVSI), parameters that are needed to define the risk group, are only available after definitive surgery, 15 , 16 such information comes too late for EC patients who may benefit from fertility‐sparing alternatives. This situation prompted research into developing biologically informative diagnostic tools to enhance the diagnosis and risk stratification of patients with EC.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional classification based on pathologic assessment includes Bokhman classification and WHO 2014 classification 9–11 can be served as an important input for (adjuvant) treatment decisions, but has proved to be unreliable and has poor reproducibility. In addition, with considerable interobserver variation, high‐grade EC cannot be reliably classified according to histomorphologic criteria, resulting in misdiagnosis due to mixed high‐grade components in histology 12–14 . Moreover, stage and lymphovascular space invasion (LVSI), parameters that are needed to define the risk group, are only available after definitive surgery, 15,16 such information comes too late for EC patients who may benefit from fertility‐sparing alternatives.…”
Section: Introductionmentioning
confidence: 99%